Dynamic modeling and operation strategy of an NG-fueled SOFC-WGS-TSA-PEMFC hybrid energy conversion system for fuel cell vehicle by using MATLAB/SIMULINK. (15th May 2019) - Wu, Zhen; Tan, Peng; Chen, Bin; Cai, Weizi; Chen, Meina; Xu, Xiaoming; Zhang, Zaoxiao; Ni, Meng
Abstract: Proton exchange membrane fuel cells (PEMFCs) are promising energy conversion devices for electrical vehicles. A reformer is needed when natural gas is used for fuel cell vehicles. The reformer can be replaced by a solid oxide fuel cell (SOFC) which can reform natural gas and produce power simultaneously, which in turn can enhance the energy efficiency. In this paper, an SOFC/PEMFC hybrid system is proposed and numerically studied to improve energy efficiency and dynamic response. A water gas shift and thermal swing adsorption subsystem is integrated into the hybrid system to ensure pure H2 for PEMFC. It is found that slow transient response of the SOFC dominates short-term dynamic behaviors, while fast response of the PEMFC governs mid-term dynamic behaviors. The results also show that the integrating thermal swing adsorption reactor and H2 buffer as a single H2 fuel source for PEMFC contributes to enhanced dynamic behaviors. The hybrid system with SOFC to PEMFC power distribution of 6:4 could stabilize output power within 20 s with a high energy efficiency of over 60% when used to power a 300 kW fuel cell vehicle. The proposed system is promising for electrical vehicle applications with enhanced energy efficiency and dynamic response. Graphical abstract: Image 103370417 Highlights: TSA based on metal hydride is introduced into SOFC-PEMFC system to purify H2 . Effect of SOFC and PEMFC power distribution on system performance is studied. Strategy of H2 buffer connecting TSA and PEMFC as a single H2 source is proposed. SOFC-WGS-TSA-PEMFC hybrid system has fast dynamic behaviors and high efficiency.